Pocket guide to accompany Emergency medical technician - Aehlert, Barbara (McGraw-Hill, 2009)
Topics include: advanced airway techniques; baseline vital signs and SAMPLE history; bleeding and shock; environmental emergencies; infant and child emergency care; legal and ethical issues; lifting and moving patients; patient assessment; pharmacology; poisoning and overdose; scene size-up; the well-being of the emergency medical technician